2001
DOI: 10.1128/iai.69.10.6411-6418.2001
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of the Aspergillus fumigatus pksP Gene Detected In Vitro and In Vivo with Green Fluorescent Protein

Abstract: Aspergillus fumigatus is an important pathogen of immunocompromised hosts, causing pneumonia and invasive disseminated disease with high mortality. To be able to analyze the expression of putative virulenceassociated genes of A. fumigatus, the use of the enhanced green fluorescent protein (EGFP) as a reporter was established. Two 5 sequences, containing the putative promoters of the pyrG gene, encoding orotidine-5-phosphate decarboxylase, and the pksP gene, encoding a polyketide synthase involved in both pigme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 34 publications
(26 reference statements)
3
59
0
1
Order By: Relevance
“…By using the enhanced green fluorescent protein, it was shown that the pksP gene was expressed during sporulation. Interestingly, this gene was also expressed in outgrowing hyphae isolated from the lungs of infected immunocompromised mice (29). This finding suggested that certain stress conditions have an effect on pksP expression.…”
mentioning
confidence: 59%
“…By using the enhanced green fluorescent protein, it was shown that the pksP gene was expressed during sporulation. Interestingly, this gene was also expressed in outgrowing hyphae isolated from the lungs of infected immunocompromised mice (29). This finding suggested that certain stress conditions have an effect on pksP expression.…”
mentioning
confidence: 59%
“…The PCR product generated was cloned into plasmid pCR2.1 (Invitrogen, The Netherlands). The DNA fragment encoding the Afyap1 gene was reisolated by cutting the recombinant plasmid obtained with BamHI and cloning the DNA fragment into plasmid pUCGH (34) to give plasmid pOtef-Afyap1-eGFP.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a 2.2-kb SmaI-SacI egfp-encoding fragment was subcloned from plasmid pUCGH (10) into the compatible EcoRV-SacI sites of plasmid pGEM-5zf(ϩ) (Promega), yielding plasmid pGfp. The 5Ј-flanking region and the open reading frame of estB were PCR amplified by using oligonucleotides oEstAf9 and oEstAf11 (including a restriction enzyme site for NcoI, which replaces the stop codon).…”
Section: Methodsmentioning
confidence: 99%